Do Changes in Body Shape Due to Pregnancy Lead to Cosmetic Surgery? A Cross-Sectional Study - Ulubasoglu, Hasan; Bakay, Kadir; Guven, Davut; Ak, Sertac; Yagmur, Caglayan; Hatirnaz, Safak; Sparic, Radmila; Tinelli, Andrea (Zeitschrift für Geburtshilfe und Neonatologie, 2022)
Objective Pregnants and puerperas show different perceptions of their body image and appearance, so authors investigated their perceptions related to pregnancy and puerperium, evaluating their views on cosmetic surgery, by a cross-sectional study.Materials and Methods 5-item questionnaires were administrated to women at first pregnancy and puerperas. Patients were submitted also to Beck Anxiety Inventory (BAI), Beck Depression Inventory (BDI) and Body Image Inventory (BII) analysis, indicating the level of anxiety, depression and body dissatisfaction for somatic changes during pregnancy and after childbirth.Results 186 healthy women, aged between 25–35 years, equally divided in pregnancy and puerperium, were compared in terms of body image, with no significant difference between groups. Analyzing the item “cosmetic surgery is required after all pregnancies”, there was a significant difference in puerperas and the item “cosmetic surgery is necessary for postpartum” was the principal. The comparison of BII, BDI, BAI values between pregnants and puerperas showed a significant difference between groups (p<0.00), with higher scores in postpartum patients.Conclusion Body shape and physical dissatisfaction during pregnancy is linked with increased risk of depression in pregnancy and puerperium, pushing women to opt for cosmetic surgery, especially in puerperium.
Keywords: pregnancy; delivery; Puerperium; body shape; cosmetic surgery